TRADISI MERDANG MERDEM KALAK KARO DI DESA JUHAR, KECAMATAN JUHAR, KABUPATEN KARO, SUMATERA UTARA - Sibero, Mada Triandala; Sibero, Diandala (Sabda: Jurnal Kajian Kebudayaan, 2017)
Juhar village is located in Subdistrict Juhar, District Karo, North Sumatera. Majority of society in Juhar village are farmers and cattlemen. A few of farmers farm in the forest and collect forest products. The society do the traditional ceremony known as merdang merdem and also known as kerja tahun. Merdang merdem in Juhar Village is organized by youth and held every year on August 17th. Merdang merdem was held as thanksgiving to the ancestral spirits for the success and good harvest. Today, merdang merdem is held for family gathering. In this event, there are traditional performances like rende and landek